Differences in factors associated with postpartum hemorrhage in developed and developing countries: A systematic review - Handayani, Sri Astuti; Kartini, Farida (Universitas Airlangga, 2025)
HIGHLIGHTS Analysis of maternal and fetal risk factors associated with postpartum hemorrhage, comparing data from both developed and developing countries. There are differences in the risk factors for postpartum hemorrhage between developed and developing countries. ABSTRACT Objective: This study aimed to assess maternal and fetal risk factors for post-partum hemorrhage in both developed and developing countries. Materials and Methods: A systematic review methodology was employed, incorporating a descriptive design. The study followed Joanna Briggs Institute (JBI) techniques, the PCC framework, and the PRISMA-ScR checklist. Article searches were conducted across four databases: Research Rabbit, Science Direct, Wiley, and PubMed. Articles published in English between 2019 and 2024 that met the inclusion criteria were selected. The search terms included combinations of “Postpartum women” OR “Puerperium” AND “Risk factors” OR